An Examination of Student Achievement in Michigan Charter Schools - Randall W. Eberts; Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 2001)
Since their inception in 1991, the number of and the student enrollment in charter schools have burgeoned. However, little attention has been paid to their effects on student achievement. Proponents hypothesize direct and indirect positive impacts of charter schools on student achievement. The direct effect is through the restructuring of teaching and learning processes. The indirect effect operates through peer effects on learning and through the market forces of competition. This paper focuses on student achievement in charter schools in Michigan. The analyses presented here suggest that students attending charter schools in Michigan are not reaching the same levels of achievement as students in traditional public schools in the same districts. Using several different models to estimate the difference between test score levels of students attending charter schools versus those from traditional public schools in the same districts, we find that students attending a charter school scored around 2 to 4 percent lower on the state's mandatory fourth grade reading and math assessments; the fifth grade students in charter schools scored about 4 percent lower on the science test and about 6 to 9 percent lower on the writing test. The models control for student, building, and district characteristics. The results are robust to several different specifications. However, many caveats are in order. Test scores are imperfect indicators of achievement. Furthermore, while we examine test scores of individual students, we are able to control for student and teacher characteristics in only a limited way and some of our explanatory variables are based on aggregate building-level and district-level information. Nevertheless, our analyses suggest that despite the fact that charter schools have the ability to introduce competition and new innovations in the provision of education, the evidence from this study implies that they will need to make up considerable ground as they become more established in order to overtake the test score levels and gains of students at traditional public schools.
Keywords: I2; J0; 330; charter; schools; education; Michigan; Eberts; Hollenbeck